Undergraduate Student Nurses’ Attitude Toward Mental Health Education: A Cross-sectional Analysis - Alsolais, Abdulellah Modhi; Areola, Benito Jr Nillo; Alfouzan, Amal; Mejia Nones, Marie Grace; Alharbi, Talal Ali (Makara Journal of Health Research, 2023)
Background: Reportedly, there has been a long-standing nursing shortage in Saudi Arabia. This study explored the attitudes of undergraduate student nurses considering them to be a factor contributing to this shortage. This study also investigated the association among gender, hospital exposures, and campus enrollment concerning mental health education. Methods: Quantitative correlational analysis was used on 124 student nurses in mental health nursing. Using Point Binary, Spearman's rank and one-way ANOVA, significant determinants were correlated to the domains of mental health nursing. Results: Student nurses have a positive attitude toward mental health education. Gender is significantly related to Preparedness for Mental Health (PMH) (r = 0.193, p = 0.032) and Course Effectiveness (CE) (r = 0.202, p = 0.024). Hospital exposures are significantly correlated to PMH (r = 0.455, p = 0.000), Knowledge on Mental Health (KMH) (r = 0.423, p = 0.000), Negative Stereotypes (NS) (r = 0.514, p = 0.000), CE (r = 0.266, p = 0.003), Anxiety Surrounding Mental Illness (ASMI) (r = 0.586, p = 0.000), and Valuable Contributions (VC) (r = 0.488, p = 0.000). A correlation was noted in campus enrollment between NS (r = 0.267, p = 0.012) and ASMI (r = 0.337, p = 0.001). Conclusions: Developing a positive attitude increases the acceptance of mental health education. Gender, hospital exposure, and course introduction positively influence students' views in selecting mental health nursing as their specialization.